PELATIHAN PENGGUNAAN LEARNING MANAGEMENT SYSTEM BERBASIS MOODLE UNTUK GURU DAN SISWA DI SMA NEGERI 2 SUKAWATI - A. A. Istri Ita Paramitha; I Nyoman Yudi Anggara Wijaya; Kadek Oki Sanjaya (UNHI Press, 2023)
When Covid-19 began to spread, which required all activities to be conducted indoors. With the development of technology, it can change the paradigm and mindset of society in seeking and processing information. Thus, this technology will have an impact on the education system. Technology can influence changes in the education system, where face-to-face learning has transformed into online learning. One educational institution that has followed the current development by implementing online learning is SMA Negeri 2 Sukawati. Despite having good information technology facilities, it is not accompanied by sufficient abilities and knowledge from teachers and students to use the Learning Management System (LMS). This becomes the background for the researchers to conduct training on the use of LMS at SMA Negeri 2 Sukawati. The training is expected to assist teachers in implementing the Moodle website at SMA Negeri 2 Sukawati.